Triage by Resource Allocation for INpatients: A Novel Disaster Triage Tool for Hospitalized Pediatric Patients. (31st January 2018) - Lin, Anna; Taylor, Kristine; Cohen, Ronald S.
Abstract: Objective: To develop a disaster triage tool for the evacuation of hospitalized neonatal and pediatric populations. Methods: We expanded an existing neonatal disaster triage tool for the evacuation of a children's hospital. We assessed inpatients using bedside visual assessments and chart review to categorize patients transport level based on local emergency medical services protocols and expert opinion. The tool was refined by using multiple Plan Do Study Act cycles. Primary outcome was the number of each level of transport required for hospital evacuation. Secondary outcome was improved efficiency of obtaining information about specific transport needs for evacuation. Results: We evaluated 1382 patients both visually and through electronic chart review over 10 random days. Accordance between visual assessment and electronic chart review reached 96.3%. During a 2 hour statewide disaster drill, no hospital units completed self-assessed transport needs for their patients; a single nurse used Triage by Resource Allocation in INpatients to determine transportation needs in less than 1 hour. ( Disaster Med Public Health Preparedness . 2018;12:692-696)